Intercellular communication in peritoneal dialysis - Sheng, Li; Shan, Yun; Dai, Huibo; Yu, Manshu; Sun, Jinyi; Huang, Liyan; Wang, Funing; Sheng, Meixiao (Frontiers in Physiology, 2024)
Long-term peritoneal dialysis (PD) causes structural and functional alterations of the peritoneal membrane. Peritoneal deterioration and fibrosis are multicellular and multimolecular processes. Under stimulation by deleterious factors such as non-biocompatibility of PD solution, various cells in the abdominal cavity show differing characteristics, such as the secretion of different cytokines, varying protein expression levels, and transdifferentiation into other cells. In this review, we discuss the role of various cells in the abdominal cavity and their interactions in the pathogenesis of PD. An in-depth understanding of intercellular communication and inter-organ communication in PD will lead to a better understanding of the pathogenesis of this disease, enabling the development of novel therapeutic targets.